Extent and Pattern of Occurrence of Natural Enemies of Lac Insect in Rangeeni strain of Katki crop around the Kuldiha Wildlife Sanctuary, Odisha - Shial, Gayadhar; Upadhyaya, Kalidas; Sahoo, Uttam Kumar; Nayak, Uma Shankar; Nayak, Saswat; Choudhury, Mantu (International Journal of Ecology and Environmental Sciences, 2024)
The extent and pattern of occurrence of natural enemies of Lac insect (Kerria lacca (Kerr.) during the rainy seasons (Katki crop) of 2017-2018 around the Kuldiha Wildlife Sanctuary, Odisha was studied. Three sites viz., agricultural fields/agroforestry, strips along the roads, and village commons (complex landscapes) differing in the degree of disturbance/landscape were chosen. Palash tree (Butea monosperma (Lam.) Taub) was the host plant for rangeeni strain of K. lacca where we observed 7 enemies (3 predators and 4 parasitoids) belonging to 6 families infesting on the lac insect. The village commons landscape had maximum number of natural enemies (predators and parasitoids) with mean number of individuals of natural enemies per 30 cm of stick lac whereas it was the least from the agricultural fields. During 2017 the prevalence of Eublemma amabilis showed the highest peak density (11.08/30 cm stick lac) in village commons followed by Pseudohypatopa pulverea (8.03/30 cm stick lac) and Chrysopa spp. (5.13/30 cm stick lac). Among the four parasitoids A. purpureus had the highest density (7.65/30 cm stick lac) as the major parasitoid whereas, Tachardiphagus tachardiae, E. tachardiae and Parechthrodryinus clavicarnis were minor parasitoids with a peak population density of 2.77, 1.77 and 1.00 per 30 cm stick lac, respectively, in village commons. However, during 2018, A. purpureus was also recorded as the major parasitoid with a peak population density (6.96 per 30 cm stick lac), whereas Tachardiphagus tachardiae, E. tachardiae and Parechthrodryinus clavicarnis were the minor parasitoids in the village commons.